PERKEMBANGAN UMKM DITINJAU DARI PEMBIAYAAN MUDHARABAH DAN MURABAHAH - Ayu Fitria; Deky Anwar; Dian Pertiwi; Fatimatuz Zuhro (I-Finance Journal, 2021)
This study aims to determine the effect of mudharabah and murabahah financing on the development of Micro, Small, and Medium Enterprises (MSMEs) in the Banyuasin Regency. The population in this study were 41 customers at the KSUS BMT Trans Mekar Sari Mandiri in Tanjung Lago, Banyuasin district. Sampling using saturated sampling (Total Sampling) with a total sample of 41 respondents. The analysis technique uses Multiple Linear Regression with hypothesis testing using the t-test and F test. The results of this study indicate that partially there is a significant influence between mudharabah financing on the development of MSMEs with a t count value of 3.258 > t table 1.68595 and a significance value of 0.002 < 0, 05. Meanwhile, murabahah financing has no significant effect on the development of MSMEs with a t-count value of 0.428 < t-table 1.68595 and a significance value of 0.671 > 0.05. The F test shows that mudharabah and murabahah financing simultaneously have a significant effect on the development of MSMEs with a calculated F value of 15.622 > 3.24 and a significance value of 0.000 < 0.05. The conclusion is that mudharabah financing partially has a significant effect on the development of MSMEs, while partially murabahah financing has no significant effect on the development of MSMEs. Simultaneously, mudharabah and murabahah financing have a significant effect on the development of MSMEs.